A comparative study of hydrothermal treatment for value-added product from various type of biomass / Aida Nadiah Hazeli and Dr Siti Sabrina Mohd Sukri - Hazeli, Aida Nadiah; Mohd Sukri, Siti Sabrina (2020)
Biomass is an abundance waste in Malaysia which comes from the plant residue, agricultural waste and forestry. İt is also known as potential feedstock that can be utilized into value-added products. However, the presence of lignin in lignocellulosic biomass must be depolymerized before cellulose and hemicellulose are converted into simple sugars. Therefore pretreatment is required to alter the structure. Different pretreatment would gives different result of composition. The objective of this study was to compare the efficiency of different pretreatment on producing value-added product from various biomass. In addition, to find a low cost, efficient and environmentally friendly pretreatment technique in producing high yield of value-added products. Basically, in this comparative study showed that percentage of lignin and hemicellulose are reduced after pretreatment. For instance, the results of pretreated bagasse with hydrothermal treatment showed 29.2% lignin from 31% and 5.4% hemicellulose from 48%. This is due to the lignin removal and hence the hemicellulose is easily hydrolyzed. However, the cellulose composition increase after pretreatment because of the solubilization of hemicellulose enhanced the enzyme accessibility of cellulose. The composition of lignocellulosic was analyzed by using the standard procedure National Renewable Energy Laboratory (NREL). Besides, the the SEM images showed that most of the lignin and hemicellulose content decreases as there was a changes on the biomass surface. It implied that all the pretreatment has done its job until the value-added product is produced. However, as referred to the goal, hydrothermal treatment does not require any chemical or catalyst and can save cost as well compared to chemical pretreatment. Therefore, hydrothermal treatment is the most convenient method for the conversion of valuable product.